A Lipschitz Stability Estimate for the Inverse Source Problem and the Numerical Scheme. (20th July 2016) - Jia, Xianzheng
Abstract : We consider the inverse source problem for heat equation, where the source term has the formf ( t ) ϕ ( x ) . We give a numerical algorithm to compute unknown source termf ( t ) . Also, we give a stability estimate in the case thatf ( t ) is a piecewise constant function.